2015
DOI: 10.1007/s40265-015-0388-8
|View full text |Cite|
|
Sign up to set email alerts
|

Panobinostat: First Global Approval

Abstract: Novartis has developed oral and intravenous formulations of panobinostat (Farydak(®)), a histone deacetylase (HDAC) inhibitor, for the treatment of cancer. HDACs have important roles in maintaining chromatin structure and in regulating gene expression, including that of tumour suppressor genes, and thus represent valid targets in the search for cancer therapeutics. Oral panobinostat is approved in the US, as combination therapy with bortezomib and dexamethasone in patients with recurrent multiple myeloma who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
116
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 46 publications
0
116
0
Order By: Relevance
“…Of note, pracinostat has been granted Orphan Drug status by the FDA for the treatment of AML 48 and panobinostat has recently received FDA approval after being granted "priority review" status for the treatment of multiple myeloma. 32,33 In this study, we demonstrated that combined panobinostat and MK-1775 treatment resulted in synergistic anti-leukemic activity in AML cell lines and ex vivo primary patient samples. In addition, we provide evidence to suggest that cooperative downregulation of CHK1 and Wee1 plays an important role in the synergistic anti-leukemic activity.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Of note, pracinostat has been granted Orphan Drug status by the FDA for the treatment of AML 48 and panobinostat has recently received FDA approval after being granted "priority review" status for the treatment of multiple myeloma. 32,33 In this study, we demonstrated that combined panobinostat and MK-1775 treatment resulted in synergistic anti-leukemic activity in AML cell lines and ex vivo primary patient samples. In addition, we provide evidence to suggest that cooperative downregulation of CHK1 and Wee1 plays an important role in the synergistic anti-leukemic activity.…”
Section: Discussionmentioning
confidence: 65%
“…Previously, we demonstrated that panobinostat, a pan-HDACI which was recently approved by the US FDA for the treatment of multiple myeloma, downregulates the CHK1 pathway in AML cells. 32,33 Also, we demonstrated that MK-1775, a potent and selective Wee1 inhibitor, synergizes with LY2603618, a CHK1 selective inhibitor, in AML cells. 34 Therefore, it is conceivable that the combination of panobinostat and MK-1775 would result in synergistic anti-leukemic activity in AML cells.…”
Section: Introductionmentioning
confidence: 75%
“…Vorinostat (SAHA; Sigma Aldrich, USA), Romidepsin (FK228; Istodax; Selleck Chemicals, USA), and Belinostat (PXD101; Beleodaq; Spectrum Pharmaceuticals, Inc., USA) are approved for cutaneous or peripheral T-cell lymphoma (Grant et al., 2007, Prince and Dickinson, 2012, Thompson, 2014), while Panobinostat (LBH-589; Selleck Chemicals, USA) is approved for combination therapy of multiple myeloma (Garnock-Jones, 2015). In this study, we assessed the capacity of all four drugs to inhibit the growth of parasites that cause malaria ( P. knowlesi ), leishmaniasis ( L. amazonensis and L. donovani ) and schistosomiasis ( S. mansoni ).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected to have a better outcome by practicing multi-drug combination in the treatment of MM. Combined with proteasome inhibitors, some HDAC inhibitors, including panobinostat and vorinostat have been shown synergistic effects in growth inhibition of MM [53,54]. It is also reported that HDAC inhibitors combined with traditional chemotherapies synergistically induced apoptosis in MM cells.…”
Section: Discussionmentioning
confidence: 99%